Arab Republic of Egypt : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report ;, 2005)
This Report on the Observance of Standards and Codes (ROSC) data module provides an assessment of Egypt's macroeconomic statistics against the Special Data Dissemination Standard (SDDS) complemented by an assessment of data quality based on the IMF's Data Quality Assessment Framework (DQAF, July 2001). The assessment reveals that against the background of economic liberalization, the Egyptian authorities have made important efforts to improve the statistics needed for developing and monitoring economic policies. There is a general awareness of the need for good quality data for these purposes.